Robust trajectory-constrained frequency control for microgrids considering model linearization error. (1st March 2023) - Zhang, Yichen; Chen, Chen; Hong, Tianqi; Cui, Bai; Xu, Zhe; Chen, Bo; Qiu, Feng
Abstract: Grid supportive modes integrated within inverter-based resources can improve the frequency response of renewable-rich microgrids. The synthesis of grid supportive modes to guarantee frequency trajectory constraints under a predefined disturbance set is challenging but essential. To tackle this challenge, a numerical optimal control (NOC)-based control synthesis methodology is proposed. Without loss of generality, a wind-diesel fed microgrid is studied, where we aim to design grid supportive functions in the wind turbine. In the control design, linearized models are used, and the linearization-induced errors are quantitatively analyzed by reachability and interval arithmetics and represented in the form of interval uncertainties. Then, the NOC problem can be formulated into a robust mixed-integer linear program. The control structure is strategically configured into two levels to realize online deployment. The proposed control is verified on the modified 33-node microgrid with a full-order three-phase nonlinear model in Simulink. The simulation results show the effectiveness of the proposed control paradigm and the necessity of considering linearization-induced uncertainty. Highlights: Novel two-level control paradigm for trajectory-constrained frequency control. Linearization error quantification for WTG models and induced bounds calculation. Robust mixed-integer linear formulation for near real-time NOC problem.